2013
DOI: 10.5194/acp-13-2735-2013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CCN activity of Arctic aerosol and Canadian biomass burning during summer 2008

Abstract: The NASA DC-8 aircraft characterized the aerosol properties, chemical composition, and cloud condensation nuclei (CCN) concentrations of the summertime Arctic during the 2008 NASA Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) campaign. Air masses characteristic of fresh and aged biomass burning, boreal forest, Arctic background, and anthropogenic industrial pollution were sampled. Observations were spatially extensive (50–85° N and 40–130° W) and exhibit si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
136
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 123 publications
23
136
1
Order By: Relevance
“…Observational studies have shown that typical atmospheric aerosols have κ between 0.1 and 0.4 (Andreae and Rosenfeld, 2008;Juranyi et al, 2010;Friedman et al, 2013;Lathem et al, 2013). For the materials considered in this study, hygroscopicity tandem differential mobility analyzer (HTDMA) measurements suggest that κ = 0.003 for both dry-and wet-generated ATD, illite, and NaMon (Herich et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Observational studies have shown that typical atmospheric aerosols have κ between 0.1 and 0.4 (Andreae and Rosenfeld, 2008;Juranyi et al, 2010;Friedman et al, 2013;Lathem et al, 2013). For the materials considered in this study, hygroscopicity tandem differential mobility analyzer (HTDMA) measurements suggest that κ = 0.003 for both dry-and wet-generated ATD, illite, and NaMon (Herich et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The assumed hygroscopicity of SOA and POM of κ soa = 0.14 and κ pom = 0.1 respectively (Table 1); however, there is a wide range of values reported for these parameters in the literature (e.g., Lathem et al, 2013). For application of Eq.…”
Section: Sensitivity Of Cdnc To Hygroscopicity Parameter Of Organic Amentioning
confidence: 99%
“…During non-IOP periods, only the total nitrate mass concentration is available, all nitrate was assumed to be an organonitrate (Cerully et al, 2015;Lathem et al, 2013;Nenes et al, 1998;Zhang et al, 2005), and sulfate was fully neutralized by ammonium (see Sect. S4.2 in the Supplement for a sensitivity study of these assumptions for non-IOP periods).…”
Section: Derivation Of Organic Aerosol Hygroscopicitymentioning
confidence: 99%
“…However, atmospheric aerosols consist of a large number of organic compounds, which often dominate the total fine aerosol mass, especially in forested areas (e.g., de Sá et al, 2017a;Zhang et al, 2007). The hygroscopicity of aerosol organics (κ org ) have been examined in both laboratory (e.g., Asa-Awuku et al, 2009;Duplissy et al, 2011;King et al, 2009;Lambe et al, 2011;Massoli et al, 2010;Raymond and Pandis, 2003) and field studies (e.g., Cerully et al, 2015;Chang et al, 2010;Dusek et al, 2010;Gunthe et al, 2009;Lathem et al, 2013;Mei et al, 2013a, b;Moore et al, 2011Moore et al, , 2012Pöhlker et al, 2016;Rose et al, 2010;Shantz et al, 2008;Wang et al, 2008). Overall, these studies show that aerosol organics exhibit a wide range of κ values from 0 to ∼ 0.3, and κ org often increases substantially during aerosol aging in the atmosphere (e.g., Duplissy et al, 2011;Lambe et al, 2011;Massoli et al, 2010;Mei et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 99%